The assembly of Institutional Pedagogy in a technical-vocational institute: training with teachers - Fabris, Luca; Zadra, Martina (Form@re - Open Journal per la formazione in rete, 2025)
The article delves into the Institutional Pedagogy (IP) class assembly as a device for working on the conflicts of everyday school life that contribute to school dropout. Starting with the informal experiments of a group of teachers from a technical and professional institute in the outskirts of Bologna, the PNRR training course on the instruments of democracy at school is reconstructed, which involved some researchers from the University of Bologna and a movement of active pedagogy teachers from the city. The life stories of students who develop a conflict with school are the epiphenomenon of a broad process rooted in inequality, welfare defunding and the consequent disintegration of social networks, and didactics can do little to address the root of the issue. The IP class assembly is one of the devices through which a real redistribution of power between young people and adults can be experimented at school, the students’ taking the floor and the collective construction of rules, with the conviction that real prevention of school dropout is built with effort and through a radical questioning of the teacher’s posture. L’assemblea della Pedagogia Istituzionale in un istituto tecnico-professionale: una formazione insegnanti. L’articolo riflette sull’assemblea di classe della Pedagogia Istituzionale (PI) come dispositivo per lavorare sui conflitti della vita scolastica quotidiana che contribuiscono alla dispersione scolastica. A partire dalle sperimentazioni informali di un gruppo di insegnanti di un istituto tecnico-professionale di Bologna, si ricostruisce il percorso di formazione PNRR sugli strumenti di democrazia a scuola che ha coinvolto alcuni ricercatori dell’Università di Bologna e un movimento di insegnanti di pedagogia attiva della città. Le storie di vita degli studenti che maturano un conflitto con la scuola sono l’epifenomeno di un processo ampio che affonda le radici nelle disuguaglianze, nel definanziamento del welfare e nella conseguente disgregazione delle reti sociali e la didattica può poco per affrontare alla radice il tema. L’assemblea di classe della PI è uno dei dispositivi attraverso cui a scuola si può sperimentare una reale redistribuzione del potere tra giovani e adulti, la presa di parola degli studenti e la costruzione collettiva delle regole, con la convinzione che una reale prevenzione alla dispersione scolastica si costruisca con fatica e attraverso una radicale messa in discussione della postura dell’insegnante.